THE CENTURY OF GLOBAL ALTERNATIVE: NEW SECURITY EXPANSE IN POST-SOVIET EURASIA - OMAROV, Nur (CENTRAL ASIA AND THE CAUCASUS, 2004)
Today it is impossible to correctly describe the present state of international relations and predict theirfuture without a careful analysis of security-related problems as an inalienable part of the world political scene. This is amply confirmed by the fact that all discussions on security problems are breaking the bounds of traditional ideas and encompassing an ever-wider area, which in turn is assuming an independent or even central role in these discussions. This is quite natural: the list of threats generated by the realities of the globalizing world and the transitional state of international relations is growing.In the 1990s, it included uneven regional development, depleting natural resources, environmental pollution, illegal migration, ethnic and religious conflicts, transnational organized crime, and international terrorism. Today we are aware of a shift from “blatant” military threats to “subdued,” mainly humanitarian, ones which are spreading to and infiltrating more than one state. This is confirmed by the growing terrorist threat felt everywhere, which is rooted, in part, in the growing economic and social inequality. Interdependence, the key term of globalization, changes the traditional nation-state’s internal and external contexts, which is leading in turn to corresponding changes in the international security sphere.s a result the security threats are changing, while the structures designed to regulate international relations and security (the U.N., OSCE, NATO, etc.) are being undermined and weakened. Indeed, they have already demonstrated their impotence in the face of new, non-military threats and their inability to handle the crises in Yugoslavia, and the Northern and Southern Caucasus. Today we should ask ourselves whether these structures can be adapted in any way to the dramatically changing world. It is equally important to ponder over the future of international relations and their role in setting up a system of international security. Discussions in recent years have testified that the present ideas about the future of international relations have not yet produced a definite answer to this question. This has happened for several reasons. Analysts and experts proceed from a varied range of methodological and theoretical approaches; states and blocs pursue interests that are difficult to harmonize. At the same time, the majority of academics and politicians agree that globalization cannot be stopped and that the world will continue to develop in this direction. This raises a question about the most probable systems of inter-national relations and their impact on all the entities involved in them. The above led me to conclude that the key features of the future world security system are taking shape in “strategic indeterminacy.”1 The term aptly describes the state the system of international relations was in at the beginning of the 1990s and means that the global security system will remain in a state of “strategic indeterminacy” for an indefinitely long transition period. While immediately after the Cold War the world had to promptly and painlessly, if possible, re-adjust to the universal values and formulate a generally acceptable answer to the new challenges and threats, today a concerted approach to the world problems remains formally recognized while the variety of positions and approaches is growing.